The Bologna Process: Discourses and dynamics of the educational reformulation in the universities of the European Union. Some reflections - Macedo, Brian (Debater a Europa, 2017)
This article proposes to analyze the Bologna Process and verify the discourses and dynamics about the reformulation of the educational offer in the universities belonging to the European Union (EU). As a methodological strategy, a review of summary literature and documentary analysis with the objective of understanding the political, economic and social effects resulting from the implementation of this new educational regime. In this sense, this study concluded that there were significant changes in the structure of universities that made progress in consolidating this reform, but also pointed to the need to follow up and restructure some of the Bologna Process guidelines so that this implementation happen satisfactorily